Prevalence and Genetic Variability of Human Polyomaviruses 6 and 7 in Healthy Skin Among Asymptomatic Individuals. (17th November 2017) - Hashida, Yumiko; Higuchi, Tomonori; Matsuzaki, Shigenobu; Nakajima, Kimiko; Sano, Shigetoshi; Daibata, Masanori
Abstract : The prevalence of human polyomaviruses 6 and 7 increased with age and in particular high viral loads were detected in the skins of elderly adults. This study also demonstrated the existence of geographically related genotypes for both viruses. Abstract: Background: Despite the pathogenetic potential of human polyomavirus 6 (HPyV6) and human polyomavirus 7 (HPyV7), they have been found in the normal skin of healthy individuals. However, little is known about the prevalence, infection levels, and geographical variations of these polyomaviruses in the skin. Methods: Using skin swabs from 470 participants aged 2–98 years, we estimated the prevalence of copy numbers of HPyV6 and HPyV7 with respect to age and ethnicity. Phylogenetic analyses were conducted based on viral sequences obtained from Asian and white populations. Results: This study provides the first analyses of the age-specific prevalence and levels of HPyV6 and HPyV7 infections in normal skin. Comparisons of age groups revealed that the prevalence and viral loads were significantly higher in elderly persons. Phylogenetic analyses demonstrated the existence of Asian/Japanese-specific strains genetically distinct from strains prevalent in the skin of the white population studied. Conclusions: This large study suggests that HPyV6 and HPyV7 infections in the skin are highly prevalent in elderly adults. Further research is warranted to understand whether persistent infection with high viral loads in the skin could be a risk factor for the development of HPyV6- and HPyV7-associated skin disorders.